Assessment of learning in chemistry: discussions required in the context of (post) pandemic (Research, Society and Development, 2021)
Learning assessment has an important role in the educational process, it goes beyond checking students' mistakes, grades, and promotion to a higher grade level or grade. It can contribute to the identification of points that need to be reviewed, both by students, during studies, and by teachers, during the (re)planning of classes, so that the development of the teaching and learning process brings benefits to everyone. In this way, considering the entire process, the assessment must be carried out throughout the school year in different ways, and not restricted to a specific time. It must be carefully planned and elaborated, especially during emergency remote teaching, when questions arise, such as: What type of assessment is possible to carry out remotely? Which instruments are the most suitable? How is it possible to have control over the cheating? How to assess post-pandemic? In order to promote reflection and debate on these issues, aimed at the evaluation process in Chemistry classes in High School, we intended this article. It is also expected that the evaluation proposals indicated in the text can contribute to the evaluation practice of Chemistry teachers working in Basic Education.